Induction of apoptosis by opium in some tumor cell lines - Khaleghi, M; Farsinejad, A; Dabiri, S; Asadikaram, G (Cellular and Molecular Biology, 2016)
The current study is aimed at investigation of the opium effects on the apoptosis of different cell lines in culture medium and compares such effects with one another. The study is carried out on over 8 cell lines (AA8, AGS, Hela, HepG2, MCF7, N2a, PC12, WEHI). A 2.86 x 10-4 g/ml opium concentration was prepared and added to the culture medium of the cell lines for 48 hours. Cytotoxicity was tested by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. The apoptotic effect of opium on the cell lines was analyzed by Annexin-PI test. Opium with concentration of 2.86 x 10-4 g/ml in 48 hours significantly induces apoptosis in certain cell lines (i.e. AA8, N2a, WEHI), apoptosis and necrosis in some others (i.e. Hela, HepG2, MCF7, and PC12), and also solely necrosis in the AGS cell line. One could infer that the usage of opium with different levels in different tissues leads to certain disorders in some tissues and may have therapeutic effects under distinctive conditions (i.e. unchecked growth of cells) as confirmed by the results.